The Importance of Community Welfare in Economic Growth Through Government Spending - Hasbiah Hasbiah; Basri Hasanuddin; Madris Madris; Anas Iswanto Anwar (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
This research is aims to provide evidence that general allocation funds and special autonomy funds effect on economic growth by mediating community welfare. The type of this research used is quantitative research with a descriptive approach. The analysis and research were carried out by using the time series data for 2018-2021 and cross-section data from 13 regencies/cities in West Papua Province. The results of this study found that the general allocation fund had a positive and significant effect on economic growth; special autonomy funds have a positive and significant impact on the welfare of the community; available allocation funds have a negative and significant effect on public interest; special autonomy funds have a positive and significant impact on the interest of the community; economic growth has a positive and significant effect on people's good; general allocation funds have a significant positive impact on people's welfare through economic development; special autonomy funds have a significant positive impact on people's interest through economic growth. It is expected that the governments will be able to recognize the potential and resources that can be developed in each region so that regions can be fiscally independent.